Gastrointestinal parasites in free grazing goats from Ayacucho, Peru: prevalence and risk factors associated with infection in herds - Palomino Guerrera, Walter (2024)
recording the location, sex, and age of the animals. The fecal samples were analyzed using the flotation technique in salt and sugar solution, and modified McMaster egg counting techniques for eggs/oocysts (epg/opg) of gastrointestinal parasites. The associations between location, sex, and age with the prevalence of gastrointestinal parasites were analyzed using the chi-square test. Fecal samples showed an overall parasite prevalence of 87.80%. The identified parasites were Eimeria spp. (86.22%), Strongyle type eggs (STE) (65.75%), Skrjabinema sp. (7.87%), Trichuris sp. (3.15%) and Moniezia spp. (3.15%). There was no significant association between the location and the presence of parasites (p<0.05), however, there was a higher prevalence and parasite variety in Luricocha. Sex and age did not have a significant association with parasitosis (p>0.05), except in prevalences of Trichurisspp. and Moniezia spp. (p<0.05). The epg/opg values revealed a higher parasite burden in goats from Colca compared to the other locations (p<0.05). There was also no statistical relationship between fecal egg/oocyst counts and sex or age, nevertheless, there were moderate and high parasitic burdens. The high prevalence of parasites such as nematodes and Eimeria spp. the need to implement strategic control and prevention programs in goats, where location and sex were found to be the most relevant risk factors for parasitosis in Ayacucho, Peru.